Bullying in a networked era: a literature review - Nathaniel Levy (SSRN eLibrary, 2012)
This research update presents an aggregation and summary of recent academic literature on youth bullying. The purpose of this document is to “translate” scholarly research for a concerned public audience, which may include but is not limited to parents, caregivers, educators, and practitioners. This translation highlights recent findings and developments in the literature and makes them accessible to the informed but non-expert reader. The document’s two guiding questions are “What is bullying?” (Section I) and “What can be done about bullying?” (Section II). Section I begins with a brief overview of key definitions and related research conversations and then addresses bullying’s prevalence, the types of individuals involved in bullying, the characteristics of individuals involved and the consequences of their involvement, and community-level dynamics related to bullying. Section II covers four areas where action has been taken to address problems associated with bullying – school policy, curricula, school climate, and parents – and ends on a note about approaches that mix or cut across these areas. The purpose is to render lessons learned from research and assessment accessible to those interested in deepening or expanding their knowledge of bullying-related issues